The Role of Angiojet™ in Acute Artery Theraphy - Dwiana Cahyaningrum; Zahra Amalia Aziz (UHAMKA Press, 2019)
THE ROLE OF ANGIOJET™ IN ACUTE ARTERY THERAPY ABSTRACT Thrombectomy device (Angiojet™) is a therapy to suck blood clot in blood vessel to be fast again with or without stenting procedure. Because of the grade of technology development is wider in vascular sector, so revascularization is the best strategy to be implenebted and one of modalities is completed by Thrombus Suction in the way to destroy the thrombus by hydrostatic pressure and then being sucked with Ventury Effect, until thrombus elimination cab be done optionally. If the blood clot is success to be sucked and clean, the next step is instalation stent to avoid collapse blood vessel and re-avoid pile of plaque. This thrombectomy position in the acute artery occlusion is there is no worry that embolism distal happens. Keywords: Thrombectomy, thrombus, arteri PERAN THROMBECTOMY DEVICE DALAM TERAPI SUMBATAN ARTERI AKUT ABSTRAK Thrombectomy device (Angiojet™) adalah terapi untuk menyedot bekuan darah pada pembuluh darah agar aliran darah menjadi lancar kembali dengan atau tidaknya tindakan stenting. Karena tingkat perkembangan teknologi semakin luas dibidang vaskular maka revaskularisasi merupakan strategi penatalaksanaan yang terbaik dan salah satu modalitasnya dilengkapi dengan Thrombus Suction dengan cara trombus dihancurkan dengan tekanan hidrostatik dan kemudian disedot dengan Ventury Effect, sehingga eliminasi trombus dapat dilakukan dengan optimal. Jika bekuan darah berhasil disedot dan bersih langkah selanjutnya adalah pemasangan stent untuk mencegah pembuluh darah kolaps dan mencegah kembali tumpukan plak. Peran Angiojet™ pada sumbatan arteri akut adalah tidak adanya kekhawatiran terjadinya emboli distal. Keywords: Trombektomi, trombus, arteri